Foam-like boron-doped g-C3N4 as acid-base cooperative catalyst for efficient nucleophilic addition in water - Jiajun Wang; Zewei Liu; Shiye Li; Chaoping Li; Su Liu; Jingwen Feng; Rong Tan (Green Chemical Engineering, 2021)
Intramolecular acid-base cooperative catalysis is a powerful strategy to promote the nucleophilic additions in synthetic chemistry, since both substrates and nucleophiles can be activated simultaneously, yielding a lower energy reaction pathway. However, the systems often suffer from catalyst quenching due to the mutual neutralization of acid/base sites. Herein, we doped the boron (B) atoms in the tri-s-triazine ring of graphite-like carbon nitride (g-C3N4) framework, to develop the acid-base cooperative catalyst for nucleophilic addition. Characterization results demonstrated a foam-like hierarchical porous structure, as well as the coexistence of Lewis acid and base sites in the as-synthesized samples. As a result, the B-doped g-C3N4 acted as the efficient acid-base cooperative catalysts, significantly promoting the Knoevenagel condensation whose key step involves in nucleophilic addition. A wide range of α, β-unsaturated carbonyl compounds with remarkably high yields (> 90%) was achieved even within 1 h in water, whereas the acid-free or base-free counterpart was far less efficient. In addition, the bifunctional catalysts exhibited excellent reusability with simple treatment. The novel B-doped g-C3N4 catalytic system offers several advantages, such as operational simplicity, mild reaction conditions, high efficiency, and facile reuse of catalyst. All these advantages make it a benign protocol from the sustainability point of view, and inspired us to design the other bifunctional cooperative catalysts for a wide range of sustainable industrial applications.